Echovirus Type 7 Virus-Associated Hemophagocytic Syndrome in a Neonate Successfully Treated With Intravenous Immunoglobulin Therapy: A Case Report - Watanabe, Yuka; Sugiura, Takahiro; Sugimoto, Mari; Togawa, Yasuko; Kouwaki, Masanori; Koyama, Norihisa; Saitoh, Shinji (Frontiers in Pediatrics, 2019)
Virus-associated hemophagocytic syndrome (VAHS) in the neonatal period has a high mortality. Although clear diagnostic criteria and treatment methods have not been established, early diagnosis and treatment are critical. However, treatments for VAHS have potentially serious side effects, especially during the neonatal period. Echovirus type 7 can cause maternal infection around parturition and be vertically transmitted to the neonate and induce VAHS. Intravenous immunoglobulin (IVIG) therapy could be a first-line therapy for neonatal VAHS, so that treatments with potentially serious side effects, including cyclosporine A and etoposide, could be avoided. A case of VAHS associated with echovirus type 7 that was successfully treated with IVIG therapy is reported.